Penerimaan Diri Pada Remaja Yang Mengalami HIV/AIDS - Siti Nurhayati (AKPER Pasar Rebo, 2018)
HIV is not only a physical problem but it also affects psychosocial problems. HIV-infected teenagers usually become denial, withdraw, fear of peer rejection, anxiety that results in poor performance in school, depression, isolation and even suicidal tendencies. The lack of information of family and community about HIV / AIDS, make this situation getting worse. One effort that can be done to overcome the problems that occur teenagers is to help develop the concept of himself positively through counseling guidance services. Multi-aspect approaches by public health groups, child specialists, schools, and community programs can reduce high-risk behavior of sex and drug abuse among teenagers